Calculation of the Intensity of Adhesive-Fatigue Wear of Cutting Tools; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Bibik V. L. Vladislav Leonidovich (2016, 2016)
Title screen